Patellar and quadriceps tendons acute repair with suture anchors - Colombelli, Andrea; Polidoro, Federico; Guerra, Giovanni; Belluati, Alberto (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Quadriceps and patellar tendon rupture are relatively uncommon but can result in a disabling condition if untreated. We retrospectively review all our cases treated with suture anchors from 2014 to 2018, to evaluate midterm outcome of this technique. Methods: Traumatic and atraumatic quadriceps and patellar tendon preinsertional lesions were acutely treated with Healix Ti and FaStin RC 5mm suture anchors and an aggressive rehabilitation protocol was prescribed to patients. Results: Good to excellent results according to the Modified Cincinnati Rating System Questionnaire was obtained at a mean 12 months followup, without major complications. Conclusions: Suture anchors are a promising alternative to transosseus suture for acute repair of quadriceps and patellar tendon lesions, but longer followups are needed for detect long-term complications.